Disability and human rights - Borea Rieckhof, Costanza (2015)
All persons are subjects of law, but not everyone has the “capacity” to fully exercise them. On this basis, people with disabilities have seen their opportunities for development as human beings limited.Why it that people with disabilities have been historically marginalized by the Law? In this article, the author presents a detailed analysis on the subject, including the legal paradigm change that was the adoption of the Convention on the Rights of Persons with Disabilities.